Cost‐effective purification process development for chimeric hepatitis B core (HBc) virus‐like particles assisted by molecular dynamic simulation - Zhang, Bingyang; Yin, Shuang; Wang, Yingli; Su, Zhiguo; Bi, Jingxiu (Engineering in life sciences, 2021)
Inserting foreign epitopes to hepatitis B core (HBc) virus‐like particles (VLPs) could influence the molecular conformation and therefore vary the purification process. In this study, a cost‐effective purification process was developed for two chimeric HBc VLPs displaying Epstein–Barr nuclear antigens 1 (EBNA1), and hepatitis C virus (HCV) core. Both chimeric VLPs were expressed in soluble form with high production yields in Escherichia coli. Molecular dynamic (MD) simulation was employed to predict the stability of chimeric VLPs. HCV core‐HBc was found to be less stable in water environment compared with EBNA1‐HBc, indicating its higher hydrophobicity. Assisting with MD simulation, ammonium sulfate precipitation was optimized to remove host cell proteins with high target protein recovery yields. Moreover, 99% DNA impurities were removed using POROS 50 HQ chromatography. In characterization measurement, we found that inserting HCV core epitope would reduce the ratio of α‐helix of HCV core‐HBc. This could be another reason on the top of its higher hydrophobicity predicted by MD simulation, causing its less stability. Tertiary structure, transmission electron microscopy, and immunogenicity results indicate that two chimeric VLPs maintained correct VLP structure ensuring its bioactivity after being processed by the developed cost‐effective purification approach.